The Invisible Economy: Personal Data as a New Commodity in the Digital Economy - Oli Gretia Nitsae (Nomico, 2026)
The digital economy has quietly transformed personal information into one of its most valuable, yet least visible, commodities. This article examines how personal data is extracted, valued, and exchanged within contemporary digital markets, framing this phenomenon as an "invisible economy" that operates behind ostensibly free services. Using a systematic narrative literature review of thirty-four peer-reviewed articles published between 2021 and 2026, drawn from Scopus-indexed and Google Scholar-accessible journals, the study synthesizes economic, legal, and sociological perspectives on data commodification. The review identifies five recurring themes: data as an economic asset, personal data markets and monetization mechanisms, platform power and surveillance capitalism, regulatory and privacy tensions, and the differentiated exposure of vulnerable groups such as children and gig workers. The novelty of this study lies in integrating fragmented disciplinary discussions into a single analytical framework that traces the full value chain of personal data, from collection to monetization to regulatory contestation. Findings indicate that despite regulatory advances such as GDPR-inspired frameworks, information asymmetry between platforms and users persists, reinforcing structural power imbalances. The article concludes that personal data functions as a pseudo-commodity whose valuation remains opaque, calling for stronger data governance, algorithmic transparency, and equitable value-sharing mechanisms in the digital economy.